Metta Brahmavihara Dharma Towards Peace Cultivation - Chatthaisang, Peerawat; Promchin พรหมชิน (Journal of Dhamma for Life, 2023)
In today’s society, there are many factors that cause conflicts to increase continually. The causes of all problems are human beings as the main factor. The principle of Brahma Vihara Dhamma is a virtue that can create unity among people in society and make the society peaceful. Metta is the first Dharma in Brahma Vihara Dharma. This pure kindness must be based on sincerity. It is the desire for others to be well and happy. It is a love that arises from a charitable and generous heart. not laced with lust, not spiteful, not vindictive Don’t expect anything in return. It is in a way that sincerely wishes and good intentions to all human beings and animals. Expressing forgiveness, trusting others and feeling connected to people as Pali says; "Loko Patthambika, Metta, Metta, Supports the World" and most importantly, when Metta Dhamma grows, it promotes the growth of other dhammas in the Brahma Vihara Dhamma, namely Metta, Karuna, Mudita, and Upekkha. Complete with covering both acrobatics, verbal and mental actions. The right actions of individuals will not cause problems and lead to conflict resolution to create unity and peace in society.